(untitled) (Journal of the College of Basic Education, 2022)
The art of acting is one of the spontaneous arts that man has practiced since ancient times, and with the music arts it was a dual that man has worked on since he knew awareness, realized, and sense of what is going on around him, and his work was like a mixture between desires and an internal premonition that a person was going through in His daily life and the hard social conditions that man used to live in his primitive surroundings, and that individual performance developed towards expressing the symbols which the rituals were full of, and the tasks assigned to him were entirely realistic, it means a sense of pure realism, which was lived by the primitive actor and the recipient He is aware of them and accepts them because they are an essential part of his reality that he was living. The sounds of drums and burning fire were an essential part of that reality that the ancient man lived in his narrow social space, and the skill in performance was collective and not individual, and this group was like One actor, not separate parts, through the use of the mask and the alternate colors that the performer used to put on his face or without all these things, the characteristics of realistic representation in that time distant era derive their origins and fundamentals from quote everything that has a lot to do with the reality that man lives, and this is what we observe in the realistic performance of Greek and Roman theatrical performances and the Renaissance, and in the present era, all the variables and changes which accompanied man’s behavior towards Every situation or phenomenon that a person goes through in his daily life which the director employs through the artistic work of events and theatrical dialogue on stage. At this point, the researcher resorted to establishing the title of his research (Aesthetics of Performance in Realistic Theatrical Performances (Selected Models), and the research consisted of four chapters, which are: Chapter One: Methodological Framework: Including the research problem that was adopted in the interrogation what are the aesthetics that the actor was able to show, highlight and clarify during his performance in embodying the dramatic character on stage? The chapter also included the importance of research and the needs for it in terms of focusing on the aesthetics of performance for the actor in realistic theater performances, and the goal of the research that seeks to discover the aesthetic elements and components in the representation of the actor in theatrical performances which are concerned with realism, and the limits of the research that were limited to the presentation of a play (Al-Arbanana: which was Written by Hamed Al-Maliki, Directed by Imad Muhammad, Acting: Aziz Khayoun, Lamia Badan, Yahya Ibrahim), which was presented at the 12th Arab Theater Festival in Sharjah: Objectively examining the aesthetics of realistic theater performances in the performance of the theater actor. The chapter concluded defines terms and their definition. The second chapter: The theoretical framework: It included two topics: The first topic: The emergence of realism in theater literature The second topic: the aesthetics of performance for the actor in the real theater In the third chapter, the researcher dealt with the research procedures, which included the research community, the research tool, and the research method, and the research sample was: The fourth chapter included research results, conclusions, recommendations, proposals, a list of sources and references, as well as an abstract in the English language.